KEARIFAN MASYARAKAT DESA PENGLIPURAN KABUPATEN BANGLI DALAM MELESTARIKAN TANAMAN BAMBU DAN APLIKASINYA SEBAGAI BAHAN BANGUNAN - I Wayan Muliawan (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2017)
ABSTRACT The resources of bamboo in Indonesia are quite potencial. Penglipuran traditional village is an integrated residential and has a unique architecture that its still existence. The concept of traditional settlement of penglipuran has no different social status and they are one in togetherness. This can be seen from the house in Penglipuran use of bamboo as building materials. This research uses descriptive qualitative methods by observation, interviews, and study literature. Utilization of bamboo house technology has a very positive impact on the utilization of natural resources and cultural preservation by local indigenous peoples. Bamboo is a basic material or material that can provide an alternative to build a house. Indigenous peoples in Penglipuran also combine bamboo round and woven so that the value of estetikapun seen together with nature. The use of bamboo material can be seen from paon, sekenem, angkul-angkul and banjar hall. Keyword: settlement, bamboo, building materials, conservation